Kyste hydatique pelvien primitif: à propos d’un cas - Bouihi, Jamal (Pan Afr Med J, 2016)
Hydatidosis is endemic in Morocco, its pelvic localization is rare and deceptive. We report the case of a 24-year old patient admitted with a giant pelvic mass associated with heaviness with no further accompanying signs. Ultrasound and CT scan allowed localization of a right lateral and subuterine septated anechoic mass. The diagnosis of pelvic hydatid cyst was made intraoperatively. Treatment consisted of resection of the protruding dome. Patient’s evolution was favorable, with a follow-up period of three years.